Integrated analyses of multi-omics reveal global patterns of methylation and hydroxymethylation and screen the tumor suppressive roles of HADHB in colorectal cancer - Yimin Zhu; Hanlin Lu; Dandan Zhang; Meiyan Li; Xiaohui Sun; Ledong Wan; Dan Yu; Yiping Tian; Hongchuan Jin; Aifen Lin; Fei Gao; Maode Lai (Clinical Epigenetics, 2018)
Abstract Background DNA methylation is an important epigenetic modification, associated with gene expression. 5-Methylcytosine and 5-hydroxymethylcytosine are two epigenetic hallmarks that maintain the equilibrium of epigenetic reprogramming. Disequilibrium in genomic methylation leads to carcinogenesis. The purpose of this study was to elucidate the epigenetic mechanisms of DNA methylation and hydroxymethylation in the carcinogenesis of colorectal cancer. Methods Genome-wide patterns of DNA methylation and hydroxymethylation in six paired colorectal tumor tissues and corresponding normal tissues were determined using immunoprecipitation and sequencing. Transcriptional expression was determined by RNA sequencing (RNA-Seq). Groupwise differential methylation regions (DMR), differential hydroxymethylation regions (DhMR), and differentially expressed gene (DEG) regions were identified. Epigenetic biomarkers were screened by integrating DMR, DhMR, and DEGs and confirmed using functional analysis. Results We identified a genome-wide distinct hydroxymethylation pattern that could be used as an epigenetic biomarker for clearly differentiating colorectal tumor tissues from normal tissues. We identified 59,249 DMRs, 187,172 DhMRs, and 948 DEGs by comparing between tumors and normal tissues. After cross-matching genes containing DMRs or DhMRs with DEGs, we screened seven genes that were aberrantly regulated by DNA methylation in tumors. Furthermore, hypermethylation of the HADHB gene was persistently found to be correlated with downregulation of its transcription in colorectal cancer (CRC). These findings were confirmed in other patients of colorectal cancer. Tumor functional analysis indicated that HADHB reduced cancer cell migration and invasiveness. These findings suggested its possible role as a tumor suppressor gene (TSG). Conclusion This study reveals the global patterns of methylation and hydroxymethylation in CRC. Several CRC-associated genes were screened with multi-omic analysis. Aberrant methylation and hydroxymethylation were found to be in the carcinogenesis of CRC.